Odds of Acute Kidney Injury in Patients Receiving Dipeptidyl Peptidase 4 Inhibitors: A National Cohort Study Within the Department of Veterans Affairs - Sutton, S. Scott (Clin Transl Sci, 2019)
Preclinical and clinical data of dipeptidyl peptidase 4 (DPP‐4) inhibitors have demonstrated discordant data regarding acute kidney injury (AKI). Therefore, we aimed to evaluate the association between DPP‐4 use and AKI. This cohort study utilized data from the Department of Veterans Affairs evaluating patients diagnosed with type 2 (T2) diabetes with a DPP‐4 inhibitor and compared with nondiabetic and diabetic patients. The primary end point is the development of AKI, and statistical analyses were performed to examine the association. DPP‐4 use is associated with a lower odds of AKI compared with diabetics (adjusted odds ratio (OR) = 0.39; 95% confidence interval (CI) = 0.32–0.48) and nondiabetics (OR = 0.64; 95% CI = 0.52–0.79). DPP‐4 use in patients with T2 diabetes mellitus is associated with lower odds of AKI within 120 days compared with nondiabetic and diabetic controls when adjusting for study covariates.